2020
DOI: 10.1038/s41419-020-2532-y
|View full text |Cite
|
Sign up to set email alerts
|

The circular RNA circMAST1 promotes hepatocellular carcinoma cell proliferation and migration by sponging miR-1299 and regulating CTNND1 expression

Abstract: Circular RNAs (circRNAs) are a class of non-coding RNAs with a loop structure; however, their functions remain largely unknown. Growing evidence suggests that circRNAs play a pivotal role in the progression of malignant diseases. However, the expression profiles and function of circRNAs in hepatocellular carcinoma (HCC) remain unclear. We investigated the expression of microtubule-associated serine/threonine kinase 1 (MAST1) circRNA (circMAST1) in HCC and healthy tissues using bioinformatics, quantitative real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 49 publications
(52 reference statements)
0
26
0
Order By: Relevance
“…5 Accumulating evidence has delineated that circRNAs possess powerful and complicated functions in varied cellular processes, involved in disease development, including cancer. 6,7 Numerous circRNAs were manifested to affect HCC progression by acting as oncogenic stimuli, like circMAST1, circMAN2B2 and hsa_circ_0091581; [8][9][10] or suppressors, such as circ-ABCB10, circRNA-0072309 and circ-0003418. [11][12][13] Derived from low density lipoprotein receptor (LDLR), circ_LDLR (ID: hsa_circ_0003892 in circBase; Position: chr19: 11,230,238,761) was reported to be upregulated in HCC tissues in contrast to non-tumor liver tissues, evidenced by searching circRNA expression profiles, GSE94508 and GSE97332.…”
Section: Introductionmentioning
confidence: 99%
“…5 Accumulating evidence has delineated that circRNAs possess powerful and complicated functions in varied cellular processes, involved in disease development, including cancer. 6,7 Numerous circRNAs were manifested to affect HCC progression by acting as oncogenic stimuli, like circMAST1, circMAN2B2 and hsa_circ_0091581; [8][9][10] or suppressors, such as circ-ABCB10, circRNA-0072309 and circ-0003418. [11][12][13] Derived from low density lipoprotein receptor (LDLR), circ_LDLR (ID: hsa_circ_0003892 in circBase; Position: chr19: 11,230,238,761) was reported to be upregulated in HCC tissues in contrast to non-tumor liver tissues, evidenced by searching circRNA expression profiles, GSE94508 and GSE97332.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, in our present study, we discovered the lncRNA NEAT1 was upregulated in 32 [29]. In addition, lncRNA HOTAIR promotes the progression of EMT by acting as a ceRNA to regulate ZEB1 expression through the sponging of miR-130a-5p in ESCC [30].…”
Section: Discussionmentioning
confidence: 51%
“…Growing evidence shows a strong relationship between epigenetic and genetic aberrations of MAST1 , PRDM14 [ 22 ], and ZNF177 [ 17 ] in tumorigenesis. Previous studies reported that abnormal MAST1 expression is significantly associated with worse cancer prognosis [ 23 , 24 ]. Oishi et al found that aberrant promoter demethylation of MAST1 could be responsible for overexpression of this gene in malignant pheochromocytoma and paraganglioma [ 25 ].…”
Section: Discussionmentioning
confidence: 99%